Matematică
silviacristina01
3

8*0:2*9*3*4+2*(101-3*8:(68-4*2*8+81:9:9*2)-96)+1=

+0
(2) Răspunsuri
Veronik31

8x0:2x9x3x4+2x(101-3x8:(68-4x2x8+81:9:9x2)-96)+1= 0+2x(101-24:(68-8x8+9:9x2)-96)+1= 0+2x(101-24:(68-64+1x2)-96)+1= 0+2x(101-24:(4+2)-96)+1= 0+2x(101-24:6)-96)+1= 0+2x(101-4)-96)+1= 0+2x(97-96)+1= 0+2x1+1= 0+2+1= 2+1=3

ruxicel25

8*0:2*9*3*4+2*(101-3*8:(68-4*2*8+81:9:9*2)-96)+1=0*2*9*3*4+2*(101-24:(68-8*8+9:9*2)-96)+1=0+2*(101-24:(68-64+1*2)-96)+1=2*(5-24:(4+2))+1=2*(5-24:6)+1=2*(5-4)+1=2*1+1=2+1=3

Adaugă răspuns